Allocative Efficiency, Mark-ups, and the Welfare Gains from Trade - HOLMES, Thomas J. (Institutional Knowledge at Singapore Management University, 2014)
This paper develops an index of allocative efficiency that depends upon the distribution of mark-ups across goods and is separable from an index of standard Ricardian gains from trade. It determines how changes in trade frictions affect allocative efficiency in an oligopoly model of international trade, decomposing the effect into the cost-change channel and the price-change channel. Formulas are derived shedding light on the signs and magnitudes of the two channels. In symmetric country models, trade tends to increase allocative efficiency through the cost-change channel, yielding a welfare benefit beyond productive efficiency gains. In contrast, the price-change channel has ambiguous effects on allocative efficiency.